Field notes contributed by Fred Lesher, fall 1998 - Lesher, Fredet al (1998)
Fall report of birds and locations contributed by Fred Lesher. This item was submitted past the deadline for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed/flatbed